Achieving Sustainable Value Planning For Malaysian Public Projects - Muhammad, Faudzi; Mahbub, Rohana; Nawawi, Abdul Hadi; Zainul Abidin, Nazirah (EDP Sciences, 2016)
Sustainability is the central development issue in the modern economy. Through sustainable development, quality of life can be improved or maintained over time. Since Malaysia is targeting to become a high-income nation by the year 2020, financial investment in public projects should be planned comprehensively so that it will generate immediate and long-term benefits to the country and the people. Within the currently tight financial environment, achieving value for money in public spending is seen as one of the enablers to maintain the right momentum of economic growth. Previous studies have established the importance of integrating sustainability consideration into Value Planning protocol in order to achieve value for money, underpinned by the sustainable development agenda. Despite the establishment of the framework for the integration, the opportunity of such integration within the Malaysian Value Planning protocol for public projects remains unclear. The present state of sustainability consideration within the Value Planning practice should be first evaluated, so that potential interventions to enhance the integration can be introduced. Responding to the gap, this exploratory study was conducted. The data was collected by means of document analysis, interviews and observations; subsequently analysed using the Template Analysis technique. Based on the current practice of Value Planning in Malaysia, ten interventions are proposed to transform the present practice into Sustainable Value Planning. Sustainable Value Planning is seen as a comprehensive concept in achieving value for money in public spending underpinned by the overarching concept of sustainability